Treatment success in cats with chronic enteropathy is associated with a decrease in fecal calprotectin concentrations - Heilmann, Romy M.; Riggers, Denise S.; Trewin, Isla; Köller, Gábor; Kathrani, Aarti (Frontiers in Veterinary Science, 2024)
Feline chronic enteropathies (FCE) are challenging to diagnose and monitor for progression and response to treatment. Fecal calprotectin might be a useful non-invasive marker to evaluate clinical endpoints of therapeutic monitoring in FCE. We evaluated fecal calprotectin concentrations in cats with FCE before and after initiation of treatment comprised of immunomodulation and/or dietary intervention. Included were 17 cats with FCE and 18 healthy controls. Clinical investigation of FCE cases included clini-cal severity grading (feline chronic enteropathy activity index, FCEAI) in all cats, abdominal ultrasonogra-phy in 15 cats, and gastrointestinal biopsies in 6 cats. Fecal calprotectin was measured in samples from 12 cats with FCE before treatment, all 17 FCE cats ≥6 weeks after treatment initiation, and all healthy controls. Fecal calprotectin concentrations in FCE cases before treatment (median: 61 μg/g) were significantly higher than after treatment initiation (median: 15 μg/g; P=0.0098) and compared to controls (median: 6 μg/g; P=0.0235) and correlated with the FCEAI scores (ρ=0.54, P=0.0316). Fecal calprotectin concen-trations after treatment initiation were higher with more severe duodenal/proximal jejunal pathology (ρ=0.83, P=0.0427) and shorter intervals between sampling time points (ρ=-0.54, P=0.0250). Relevant decreases in initially increased fecal calprotectin concentrations are seen in cats with FCE on varying treatment strategies that significantly improve or have remission of clinical signs. This supports the utility of fecal calprotectin as a surrogate biomarker to assess disease severity in FCE cases. Further studies need to evaluate fecal calprotectin concentrations longitudinally in relation to mucosal healing vs. clinical response.